Estimation of Raindrop Size Distribution Parameters Using Rain Attenuation Data from a Ku-Band Communications Satellite - Indrayani, Wira; Marzuki,; Vonnisa, Mutya (UI Scholars Hub, 2016)
The rain attenuation of down-link radio wave signals from the Superbird-C satellite and surface rainfall data have been used to estimate the parameters of exponential raindrop size distribution (DSD) at Koto Tabang (100.32 °E, 0.20 °S), West Sumatra, Indonesia. Prior to analyzing the measured data, the ability of the method to recover the parameters of known DSDs from which the samples were taken was examined. It was found that the method can accurately retrieve the input parameter of the sample. Only six case studies are presented here, so the results are representative rather than definitive. The method successfully estimated the DSD parameters of a stratiform case with steady intensity and deep convective rains of a short duration. This can be inferred from the small difference between the parameters derived from rain attenuation data and those derived from a 2D video disdrometer. The poor performance of the method was observed for a stratiform case with strong rain intensity fluctuation and shallow convective rains with very low rain top height. This phenomenon is probably due to the bias that may be inherent in the estimation of specific rain attenuation, such as the assumption of a constant path length throughout the rain.